Using the Software to Registers of Health Problems and Management in Health Care Herds of Cattle - Tomáš Frejlach; Miloslav Šoch; Luboš Zábranský; Luboš Zábranský; Anna Poborská; Anna Švarcová; Kateřina Švejdová; Zuzana Křížová (Scientific Papers Animal Science and Biotechnologies, 2023)
The registers of the use of veterinary medicines are obliged breeder and veterinarians by Decree 344/2008 Coll. law 378/2007 Coll. In the Czech Republic there are still farms where the registers of used medicaments and performed veterinary care are done by hand in notebooks or in paper form. As a result of the multiple data overwriting thus leads to introducing additional errors and the process information processing is considerably extended. Software for healthcare registers of animals using the same technology as the system of registration of animals Skotsoft. The introduction of the new system would facilitate the whole zootechnical registers and accelerate the entire data processing. In the event, that a customer used the registers of animals and healthcare registers, there is mutually exchanged information between systems. It is not necessary, for example, to enter basic information about the animal (identification number, date of birth, gender, etc.) into each system separately. The advantage of both systems is the same graphical interface and control.